Management of High Fiber Induced Diarrhoea in Kittens – A Case study - Sudhakara Reddy, Bhavanam; Sivajothi, Sirigireddy; Swetha, Kambala (Indian Journal of Veterinary Medicine, 2024)
Kitten diarrhoea is one of the common clinical presentations and it is caused by multiple etiopathology. One of the poorly documented etiologies is high fiber-induced diarrhoea in kittens. The present study reports diarrhoea in eight kittens aged about three months in a single house which were regularly dewormed and vaccinated and daily fed with a commercial available diet with high fiber (5%). Cats were reported to be passing watery and odorless stools for the past week in spite of treatment with antibiotics and supportive medications. Clinical examination revealed dehydration, dullness and poor body condition. Faecal samples examination did not reveal any parasitic ova. Based on the history, clinical and laboratory examination the condition was diagnosed as high fiber induced diarrhoea in kittens and was successfully recovered with the shift of diet to low fiber and supplements of probiotics.